Analisis Penggunaan Butterworth pada Saat Proses Tank Cleaning Di MT. Marina Prospeirty - Kharisma Maula Aditya Basri; A.A Ngurah Ade Dwi Putra Yuda; Dian Junita Arisusanty; Samsul Huda (Pusat riset dan Inovasi Nasional, 2026)
This research is motivated by the importance tank cleaning process on tankers to prevent cargo contamination, maintain cargo quality, and ensure crew safety. MT. Marina Prosperity, a chemical/oil tanker, uses the Butterworth system as the primary method for tank cleaning at every cargo change. However, in practice, technical and operational constraints are still found that affect the results of tank cleaning. The research method used is descriptive qualitative with data collection techniques through direct observation on the ship, interviews with the Chief Officer and Boatswain, and documentation studies in the form of log books and SOPs. Data were analyzed by focusing on three aspects, namely work efficiency, work safety, and operational procedures for using Butterworth. The results show that the use of Butterworth can increase time and energy efficiency compared to manual methods, with an average cleaning time of 2–4 hours per tank depending on the type of cargo. From a safety aspect, Butterworth reduces the need for crew to enter the tank, thereby reducing the risk of exposure to chemicals and hazardous atmospheres. However, work effectiveness and safety are greatly influenced by the condition of the equipment, the stability of water pressure, and the crew's discipline in implementing the SOP. On several occasions, steps such as nozzle cleaning, manual mopping, and safety meetings were not consistently performed, resulting in residual load in certain areas. With routine equipment maintenance, close supervision, and ongoing crew training, Butterworth can be optimized to produce more effective, safe, and standards-compliant tank cleaning process.